Studies of the interaction of ticagrelor with the P2Y13 receptor and with P2Y13-dependent pro-platelet formation by human megakaryocytes - Björquist, Anna; Di Buduo, Christian A.; Femia, Eti A.; Storey, Robert F.; Becker, Richard C.; Balduini, Alessandra; Nylander, Sven; Cattaneo, Marco (Thrombosis and Haemostasis, 2016)
Ticagrelor is an antagonist of the platelet P2Y12 receptor for ADP, approved for the prevention of thromboembolic events in patients with acute coronary syndrome. Previous studies showed that ticagrelor has no significant activity versus P1 receptors for adenosine and other known P2Y receptors, with the exception of P2Y13, which was not tested. The P2Y12 antagonist cangrelor has been shown to also inhibit P2Y13 and to decrease the P2Y13-regulated capacity of megakaryocytes to produce pro-platelets. We tested whether or not ticagrelor inhibits P2Y13 signalling and function. The in vitro effects of ticagrelor, its active (TAM) and inactive (TIM) metabolites, cangrelor and the P2Y13 antagonist MRS2211 were tested in two experimental models: 1) a label-free cellular response assay in P2Y13-transfected HEK293 T-REx cells; and 2) pro-platelet formation by human megakaryocytes in culture. Ticagrelor, TAM, cangrelor and MRS2211, but not TIM, inhibited the cellular responses in P2Y13-transfected cells. In contrast, only MRS2211 and cangrelor, confirming previous results, inhibited pro-platelet formation by megakaryocytes in vitro. The platelet count of patients randomised to treatment with ticagrelor in the PLATO trial did not change during treatment and was comparable to those of patients randomised to clopidogrel. In conclusion, ticagrelor and TAM act as P2Y13 antagonists in a transfected cell system in vitro but this does not translate into any impact on pro-platelet formation in vitro or altered platelet count in patients.
Keywords: Ticagrelor; P2Y12; P2Y13; megakaryocytes; platelets